Post-Quantum Cryptography in Satellite Internet: Applications and Reflections - HUANG Boxue; GU Xin; SHAN Chao; SU An (天地一体化信息网络)
With the ongoing development of quantum computers, the security of satellite Internet faces significant challenges. This paper first introduced the basic concepts of satellite Internet and post-quantum cryptography, thoroughly analyzed the security needs of satellite Internet under the threat of quantum computing. By reviewed the current research status of post-quantum cryptography both domestically and internationally, this paper explored the characteristics and application potential of various post-quantum cryptographic approaches, included lattice-based, code-based, hash-based, and multivariate-based techniques. Through comparative analysis, a post-quantum security architecture suitable for satellite Internet was proposed, laid the groundwork for addressing future quantum computing threats. Finally, the paper discussed the main security issues and challenges that satellite Internet may face in the quantum computing era and proposed corresponding countermeasures.